Effects of Intra-articular Bone Marrow Aspirate Infiltration in the Treatment of Knee Osteoarthritis: A Clinical Study Comparing BMA versus Corticosteroid and Genicular Block - Clazzer, Renata; Pinto, Dilamar Moreira; Krause, Mariana Valois de Aquino; Rolim, Tale Lucas Vieira; Oliveira, Ricardo Lyra de; Ariel de Lima, Diego (Revista Brasileira de Ortopedia, 2025)
Objective To assess the efficacy of autologous bone marrow aspirate (BMA) in reducing pain and improving functionality in patients with knee osteoarthritis (OA), in comparison with intraarticular corticosteroid injection and genicular nerve block.Methods A prospective, randomized, controlled, single-blinded, comparative, and analytical clinical study was conducted. There were 50 patients with knee OA divided into two groups: an intervention group receiving BMA treatment and a control group undergoing standard corticosteroid articular infiltration and genicular block. Outcome measures were evaluated using the Western Ontario and McMaster universities osteoarthritis index (WOMAC).Results After 6 months, significant pain reduction was noted in the BMA group compared with the control group (p = 0.030). No significant differences were found in stiffness and physical activity scores between the groups. The intervention group demonstrated significant improvements in all assessed WOMAC subcategories pre- and posttreatment.Conclusions Treatment with BMA can significantly reduce pain, potentially leading to an improved functionality, suggesting its potential as a viable therapeutic option for managing knee OA.
Keywords: bone marrow; injections, intra-articular; osteoarthritis, knee; pain management